S Velocity Probing of Ontong-Java Plateau by Analyzing Seismograms of B041196C Earthquake - Bagus J. Sentosa (IPTEK, LPPM, Institut Teknologi Sepuluh Nopember, 2009)
This research investigates the S wave velocity structure under Ontong-Java Plateau in Equator Western Pacific using seismogram analysis of B041196F earthquake at various observatory stations. The analyzed wave phases are the S wave, Love and Rayleigh surface wave phases and core reflected ScS and ScS2 wave phases. Seismogram comparison shows different discrepancies that depend on the azimuth direction from hypocenter. South East area of OJP has positive anomaly that differs from the other previously seismological research in the same area. Eastwards area of OJP has negative anomaly like the other result of seismological research. On other azimuth direction indicates that positive anomaly occurred not only in the upper mantle but also at mantle layers till CMB.